Case–case comparison of smoking and alcohol risk associations with Epstein–Barr virus‐positive gastric cancer. Issue 4 (28th August 2013) - Camargo, M. Constanza; Koriyama, Chihaya; Matsuo, Keitaro; Kim, Woo‐Ho; Herrera‐Goepfert, Roberto; Liao, Linda M.; ,; Yu, Jun; Carrasquilla, Gabriel; Sung, Joseph J.Y.; Alvarado‐Cabrero, Isabel; Lissowska, Jolanta; et al.
<x xml:space="preserve">Abstract</x> Helicobacter pylori is the primary cause of gastric cancer. However, monoclonal Epstein–Barr virus (EBV) nucleic acid is also present in up to 10% of these tumors worldwide. EBV prevalence is increased with male sex, nonantral localization and surgically disrupted anatomy. To further examine associations between EBV and gastric cancer, we organized an international consortium of 11 studies with tumor EBV status assessed by in situ hybridization. We pooled individual‐level data on 2, 648 gastric cancer patients, including 184 (7%) with EBV‐positive cancers; all studies had information on cigarette use (64% smokers) and nine had data on alcohol (57% drinkers). We compared patients with EBV‐positive and EBV‐negative tumors to evaluate smoking and alcohol interactions with EBV status. To account for within‐population clustering, multilevel logistic regression models were used to estimate interaction odds ratios (OR) adjusted for distributions of sex (72% male), age (mean 59 years), tumor histology (56% Lauren intestinal‐type), anatomic subsite (61% noncardia) and year of diagnosis (1983–2012). In unadjusted analyses, the OR of EBV positivity with smoking was 2.2 [95% confidence interval (CI) 1.6–3.2]. The OR was attenuated to 1.5 (95% CI 1.01–2.3) by adjustment for the possible confounders. There was no significant interaction of EBV status with alcohol drinking (crude OR 1.4; adjusted OR 1.0). Our data indicate the smoking association with gastric cancer is stronger for EBV‐positive than EBV‐negative tumors. Conversely, the null association with alcohol does not vary by EBV status. Distinct epidemiologic characteristics of EBV‐positive cancer further implicate the virus as a cofactor in gastric carcinogenesis.